Explanation of the planning of elderly-friendly urban spaces, a case study: Hezar Jarib neighborhood - Setareh Nekooei; Hamid Saberi (مهندسی و مدیریت ساخت, 2021)
From the past to the present, the elderly are the most sensitive and vulnerable part of any society, which should be taken into consideration by the city authorities into provide the best social and welfare conditions for them in their living environment. The purpose of this research is to evaluate the urban spaces of Hazarjarib neighborhood based on the indicators of an elderly-friendly city in line with planning to meet the needs of the elderly in this neighborhood. For this purpose, the indicators of the elderly-friendly city, which are divided by the World Health Organization into 8 components of open space and buildings, housing, transportation, social participation, respect and social inclusion, civic participation and employment, communication and information, and health services, have been examined. Due to the nature of the method, this article is quantitative and in terms of practical purpose, it is a descriptive-analytical research in which data has been collected from two documentary-library, field and survey methods. The statistical population of the research is the citizens of 60 years and older of Hazarjarib neighborhood of Isfahan; For this purpose, the sample size was determined through random sampling and using Cochran's formula, and 346 questionnaires were provided to the citizens. Then, using spss tool, information was extracted from the questionnaires. In the next step, the extracted data were analyzed and evaluated through inferential statistics such as one-sample T-test, independent T-test, Pearson's correlation test and Friedman's test. The findings of this research show that, in general, the status of the indicators of the elderly-friendly city in Hazarjerib neighborhood has been evaluated as unfavorable from the point of view of the elderly, and among the eight indicators examined in the research, only three indicators of open space and buildings, housing, and transportation were in a favorable condition in the neighborhood.